APPLICATION RESEARCH ON LOAD SPECTRUM OF STEERING KNUCKLE MULTI-AXIS VIRTUAL TEST BENCH (MT) - DU Jian; HUANG LiMei; WEI MinXian; DONG GuoJiang (Jixie qiangdu)
To explore an accurate load spectrum editing method and discover the influence of different types of bench load spectrum on steering knuckle fatigue damage, the verified test field load spectrum was used as the data source and the knuckle endurance specification was simplified. The multi-body dynamics model of the vehicle was verified by the Kinematics Compliance（KC） test of the suspension and virtual iteration method. The bench random spectrum with the features of time and frequency domain was created by the domain editing method. Four-stage bench program spectrum was generated by damge equivalence principle. According to the result of the statistical knuckle’s pseudo damage in all directions and the modal test, the knuckle multi-axis virtual bench was built. The modal stress recovery method is used to compare the fatigue damage under the steering knuckle of the original spectrum, the bench random spectrum, and the bench program spectrum. The result shows that the damage distribution under the three excitations is consistent. The maximum damage ratios of the bench random spectrum and bench program spectrum to the original spectrum were 0.75 and 1.7, the accuracy of the load spectrum editing method and the engineering practicability of the virtual bench are verified. Finally, the load type of the steering knuckle fatigue damage and the road type were determined through the virtual bench transfer matrix, which provides data support for structural improvement.